Les images en géographie sous l’angledes humanités numériques - Gaëlle Hallair (EchoGéo)
This article points out the methodology of Digital humanities to preserve, to stock, to make an inventory, to digitize, to index, to enhance the value und to spread geographical archives. It applies this methodology to geographical visual documents and presents a database project about photographic plates of the Emmanuel de Martonne’s collection localised in the research center PRODIG (UMR CNRS 8586).